Perforated Jejunal Diverticulum - an Unusual Presentation (Journal of Patan Academy of Health Sciences, 2015)
Jejunal diverticula are rare and usually asymptomatic. Acute complications may include haemorrhage, diverticulitis, obstruction, abscess formation and perforation. Here we report a case of 61 years lady who presented with generalized abdominal pain, vomiting and fever. There were features of acute peritonitis on examination. Exploratory laparotomy revealed a perforated jejunal diverticulum. Resection of the jejunal segment containing the perforated diverticulum and primary anastomosis was done. Histopathological examination revealed jejunal diverticulum with pinhole perforation. DOI: http://dx.doi.org/10.3126/jpahs.v1i1.13016   Journal of Patan Academy of Health Sciences. 2014 Jun;1(1):43-45